دور التحول الرقمي في تحسين الأداء الإداري: دراسة تطبيقية على مصرف التجاري الوطني – فرع صرمان - محمد علي مبارك المنوبي (Surman Journal of Science and Technology, 2026)
This study aims to analyze the role of digital transformation in enhancing the administrative performance of employees at the National Commercial Bank – Sorman Branch. It examines the impact of digital infrastructure and the challenges associated with digital transformation on the efficiency and quality of administrative performance. The study adopted a descriptive-analytical approach, and data were collected using a questionnaire distributed to a sample of (20) bank employees. The results revealed a high level of digital transformation implementation within the bank, particularly regarding digital infrastructure. Furthermore, the findings indicated a statistically significant positive impact of digital transformation on improving administrative performance efficiency in terms of task completion speed, data accuracy, and decision-making quality. Conversely, the study identified notable challenges, most prominently resistance to change among some employees, a lack of specialized training, and certain technical infrastructure weaknesses. The study recommends the necessity of strengthening digital training programs, further developing technical infrastructure, and fostering a culture of digital transformation within banking institutions.